"Are you still driving?" Metasynthesis of patient preferences for communication with health care providers. (18th May 2016) - Betz, Marian E.; Scott, Kenneth; Jones, Jacqueline; Diguiseppi, Carolyn
ABSTRACT: Aim : The aim of this study was to synthesize published qualitative studies to identify older adults' preferences for communication about driving with health care providers. Background : Health care providers play a key role in addressing driving safety and driving retirement with older adults, but conversations about driving can be difficult. Guides exist for family members and providers, but to date less is known about the types of communication and messages older drivers want from their health care providers. Design : A qualitative metasynthesis of studies published on or before October 10, 2014, in databases (PubMed, CINAHL, PsycINFO, and Web of Science) and grey literature was performed. Review Methods : Twenty-two published studies representing 518 older adult drivers met the following inclusion criteria: the study (1) was about driving; (2) involved older drivers; (3) was qualitative (rather than quantitative or mixed methods); and (4) contained information on older drivers' perspectives about communication with health care providers. Results : We identified 5 major themes regarding older adults' communication preferences: (1) driving discussions are emotionally charged; (2) context matters; (3) providers are trusted and viewed as authority figures; (4) communication should occur over a period of time rather than suddenly; and (5) older adults desire agency in the decision to stop driving. Conclusion : Various stakeholders involved in older driver safety should consider older drivers' perspectives regarding discussions about driving. Health care providers can respect and empower older drivers—and support their family members—through tactful communication about driving safety and mobility transitions during the life course.